2011
DOI: 10.1055/s-0031-1283176
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory and Neuromuscular Responses during Water Aerobics Exercise Performed with and without Equipment

Abstract: The aim of the study was to compare the cardiorespiratory and neuromuscular responses to water aerobics exercise performed with and without equipment. 15 women performed stationary jogging combined with elbow flexion/extension without equipment, with water-drag forces equipment and with water-floating equipment, at 2 submaximal cadences and at maximal cadence. Heart rate, oxygen uptake and electromyographic signal from biceps brachii, triceps brachii, biceps femoris and rectus femoris were collected during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
21
0
2
Order By: Relevance
“…[68][69][70][71] Recent studies have reported a more accurate self-regulated approach to prescribing intensity during aquatic resistance exercises through visual and verbal perceptual cuing systems that include a RPE scale. 72 To elicit these intensity-dependent physiological responses during aquatic HIIT, systematic manipulation of several potential modulators are recommended and may include the following: (1) changing body position; (2) segmental actions of upper and lower limbs; 73 (3) increasing speeds and surface area of the movement patterns that are executed; [73][74][75] or (4) adding equipment such as gloves, paddles, bands, or other resistive devices 74,76,77 (refer to Sidebar 1). response typically results in a 12% to 15% decrease in HR.…”
Section: Hydrostatic Pressurementioning
confidence: 99%
“…[68][69][70][71] Recent studies have reported a more accurate self-regulated approach to prescribing intensity during aquatic resistance exercises through visual and verbal perceptual cuing systems that include a RPE scale. 72 To elicit these intensity-dependent physiological responses during aquatic HIIT, systematic manipulation of several potential modulators are recommended and may include the following: (1) changing body position; (2) segmental actions of upper and lower limbs; 73 (3) increasing speeds and surface area of the movement patterns that are executed; [73][74][75] or (4) adding equipment such as gloves, paddles, bands, or other resistive devices 74,76,77 (refer to Sidebar 1). response typically results in a 12% to 15% decrease in HR.…”
Section: Hydrostatic Pressurementioning
confidence: 99%
“…Buoyancy force combined with the size of the floating device means that a lower velocity is reached and therefore the resulting end force is maintained. Pinto et al (27) analyzed 15 women performing stationary jogging combined with elbow flexion and extension without devices, with a drag device and with a floating device at maximum cadence, and the results showed no significant differences between the performance of the exercise with or without devices for most muscles evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…All records of myoelectrical activity (in microvolts) were stored on a hard drive for later analysis. The insulation procedures have been described previously by Pinto et al (27), and this technique was performed to avoid interference because of the contact of electrodes with water, which can produce noise in the EMG signal. To acquire the surface EMG signals produced during exercise, an ME6000P8 (Mega Electronics, Ltd., Kuopio, Finland) biosignal conditioner was used.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown high EMG reliability for aquatic exercises. 18,33,34 To acquire the surface EMG signals produced during exercise, an ME6000P8 (Mega Electronics, Ltd., Kuopio, Finland) biosignal conditioner was used.…”
Section: Experimental Sessionmentioning
confidence: 99%